Impact of irrigation water deficit on two tomato genotypes grown under open field conditions: From the root-associated microbiota to the stress responses - Sillo, Fabiano; Marino, Giovanni; Franchi, Elisabetta; Haworth, Matthew; Zampieri, Elisa; Pietrini, Ilaria; Fusini, Danilo; Mennone, Carmelo; Centritto, Mauro; Balestrini, Raffaella (Italian Journal of Agronomy, 2022)
In the context of the climate change scenario in the Mediterranean, natural root-microorganism associations have an impact on the resilience and productivity of crops, and the exploitation of these interactions represents innovative, cost-effective and sustainable crop adaptation strategies. An open field experiment with two commercial Italian tomato cultivars was performed. The soil bacterial communities associated with the two commercial Italian tomato genotypes were characterized alongside their physiological and molecular responses under wellwatered and moderate water deficit (100% and 75% of crop evapotranspiration) treatments. The two genotypes showed contrasting responses to water deficit, primarily through diverse rhizosphere microbiota recruitment under the two irrigation treatments. Highlights - Two tomato genotypes were studied under water deficit in a pilot field trial. - The two genotypes responded differently to water stress from eco-physiological and transcriptomic points of view. - The two genotypes recruited diverse root-associated microbiota, particularly under water deficit.